The proportion of circulating CD45RO+CD8+ memory T cells is correlated with clinical response in melanoma patients treated with ipilimumab - Tietze, Julia K.; Angelova, Daniela; Heppt, Markus V.; Reinholz, Markus; Murphy, William J.; Spannagl, Michael; Ruzicka, Thomas; Berking, Carola (European Journal of Cancer, 2017)
Background Immune checkpoint blockade (ICB) has been a breakthrough in the treatment of metastatic melanoma. But with only about 20–40% long-term responders and severe side-effects in about 12–17%, finding predictive markers for treatment response is of great interest. Methods We prospectively assessed clinical data, haematologic parameters and freshly isolated peripheral blood mononuclear cells of 30 patients treated with ipilimumab (n = 21) and pembrolizumab (n = 9) prior to the first 4 cycles with ICB and before the first tumour assessment. Results We discovered that the baseline levels of CD45RO+CD8+ T cells significantly differed among the patients. Thirteen (43%) of our patients had normal baseline levels of CD45RO+CD8+ T cells, whereas 17 (57%) patients were low on CD45RO+CD8+ T cells. The baseline levels of CD45RO+CD8+ T cells correlated significantly with the response to ipilimumab but not pembrolizumab. Patients with baseline levels of lower/equal 25% of CD45RO+CD8+ T cells did not respond to treatment with ipilimumab. Phenotyping the CD8+ T cells in patients treated with ipilimumab revealed an activated HLA-DR+CD25− phenotype, implying antigen non-specific stimulation. The levels of the HLA-DR+CD25−CD8+ T cells were significantly higher in patients with a normal baseline of CD45RO+CD8+ T cells and even increased significantly during treatment. Furthermore, proliferation of melanoma antigen recognized by T cells 1 (MART-1)-specific CD8+ T cells was not observed. Patients with normal baseline levels of CD45RO+CD8+ T cells showed a significant longer overall survival when treated with ipilimumab but not pembrolizumab. Conclusion Patients with normal baseline levels of CD45RO+CD8+ T cells respond significantly more frequently to treatment with ipilimumab and the CD8+ T cells appear to be antigen non-specifically activated. The baseline level of CD45RO+CD8+ T cells represents a promising factor as biomarker for the prediction of the response to ipilimumab.
CRIS-Team Scopus Importer:2023-03-23
Keywords: CD45RO; HLA-DR; Immune checkpoint blockade; Ipilimumab; Melanoma; Pembrolizumab; Predictive marker